The Influence of Open Plan Office on the Work Productivity of KMP LAN Puslatbang Employees - Niswaty, Risma; Vebriani, Nunu; Arhas, Sitti Hardiyanti (Pinisi Journal of Officers Review, 2024)
Open plan office is one type of office layout applied by Puslatbang KMP LAN to arrange rooms, equipment, equipment, and furniture to create comfort in several aspects that affect employee productivity. The purpose of this study is to describe spatial planning, characterize employee productivity, and determine the impact of spatial planning on employee productivity. The type of research approach used is based on quantitative and qualitative research methods. Data collection methods such as observations, questionnaires and documents were used to achieve the objectives of this study. This study was conducted on 52/60 employees, and the method of determining the sample used was non-probability sampling, namely simple random sampling. The collected survey data is analyzed using statistical analysis, testing classical assumptions. in particular Kolmogorov Smirnov's conventional tests, and inferential statistical analysis to determine whether open office design has an impact on productivity or not. The results showed that the indicators used for each variable in the implementation of the open office scheme were in the medium category, while employee productivity was in the good category. Several indicators of open space planning are used: the principle of the shortest route, working order, utilization of the entire area, changes in the arrangement of the workplace. While employee productivity indicators include ability, performance improvement, morale, self-development, quality, and efficiency. Based on the results of the product moment correlation analysis, the relationship between variables is included in the medium category. Based on the results of the simple linear regression process carried out, it can be concluded that spatial planning has a positive and significant effect on the productivity of employees of the Makassar KMP LAN puslatbang.